Molecular Detection of Second Internal Transcribed Spacer (ITS-2) Encoding Gene Sarcoptes scabiei of Stray Cat from Several Market in Bondowoso - Rusdiana, Nur; Wibawati, Prima Ayu; Retno Lastuti, Nunuk Dyah; Amukti, Pandu Tokoh (Jurnal Medika Veterinaria, 2025)
Scabies is an infectious disease which is caused by Sarcoptes scabiei mites and considered as an emerging/re-emerging parasitic disease. Recent study using the Polymerase Chain Reaction (PCR) method has a higher sensitivity for detecting mites than using the skin scraping method. This study aims to detect the Second Internal Transcribed Spacer (ITS-2) encoding gene of S. scabiei. ITS-2 is a highly conserved area and always used to identify and differentiate host species infected by S. scabiei. S. scabiei isolates were obtained from skin scrapings from stray cat suspected of being infected with Scabies from Pasar Induk Bondowoso, Pasar Tamanan and Pasar Pujer. Detection on the presence of S. scabiei was carried out microscopically and then confirmed by molecular examination using the PCR method and visualized by electrophoresis on 2% agarose gel. The Polymerase Chain Reaction (PCR) results showed DNA bands at 304 bp Based on the result it can be concluded that samples are positively infected by Scabies can be detected by the ITS-2 encoding gene of Sarcoptes scabiei.